2017
DOI: 10.1186/s13075-017-1409-7
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of lung ultrasound B-lines in connective tissue disease-associated interstitial lung disease: a literature review

Abstract: Interstitial lung disease (ILD) is a major pulmonary manifestation of connective tissue disease (CTD), leading to significant morbidity and mortality. Chest high-resolution computed tomography (HRCT) is presently considered the diagnostic gold standard for pulmonary fibrosis diagnosis and quantification in the clinical arena. However, not negligible doses of ionizing radiation limit the use of HRCT, especially for serial follow-up in younger female patients. In the past decade, lung ultrasound (LUS) has been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 42 publications
3
89
1
5
Order By: Relevance
“…On the other hand, weaknesses of this paper compared with previous works [18,23,[32][33][34] are the lack of information about basal posterior areas, usually the more involved and more informative in the case of IPF patients, the lack of data about respiratory function tests [32], and the lack of ultrasound evaluations of the pleural line performed with linear probes.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…On the other hand, weaknesses of this paper compared with previous works [18,23,[32][33][34] are the lack of information about basal posterior areas, usually the more involved and more informative in the case of IPF patients, the lack of data about respiratory function tests [32], and the lack of ultrasound evaluations of the pleural line performed with linear probes.…”
Section: Discussionmentioning
confidence: 86%
“…An acoustic map of the peripheral lung is already possible based on these considerations. Echographic scans with a pattern of SIS displaying vertical artifacts prevailing on horizontal phenomena and altered pleural line is in fact indicative of important fibrotic alterations in the peripheral parenchyma [22,23]. Moreover, if, in correspondence of a specific landmark, a LUS pattern 1 changes towards a LUS pattern 3 in a subsequent evaluation over time, this could be indicative of a progression of the diseases in that specific point, and guide the timing of HRCT scan re-evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Lung ultrasonography findings have a high sensitivity (89%-97%) but varying specificity (50%-97%) compared to HRCT in patients with RA-ILD [52,53]. However, the etiology of the B lines may be difficult to establish in clinical practice, and differentiation between inflammatory and fibrotic changes is not possible using LUS [54].…”
Section: Imagingmentioning
confidence: 99%
“…B-Lines are a new sonographic hallmark of connective tissue disease–associated interstitial lung diseases (CTD-ILDs). Promising data have shown that B-lines are associated with high-resolution CT (HRCT), pulmonary function test and some clinical variables, expanding the armamentarium for screening of ILDs 1. Krebs von den Lungen-6 (KL-6) antigen is a mucin-like, high molecular weight glycoprotein expressed on the surface membrane of alveolar epithelial cells Ⅱ and bronchiolar epithelial cells, and increases following cellular injury and/or regeneration 2.…”
mentioning
confidence: 99%